RESPONSE OF EARLY CRETACEOUS CARBONATE PLATFORMS TO CHANGES IN ATMOSPHERIC CARBON DIOXIDE LEVELS - Wissler L.; Funk H.; Weissert H. (My University, 2003)
During the Late Barremian and Early Aptian (about 120 million years ago) intense volcanic degassing and extremely rapid release of methane hydrates contained in marine sediments added high amounts of carbon to the ocean and atmosphere, and resulted most probably in rising atmospheric carbon dioxide pressure. In order to document the response of the shallow water carbonate-producing communities to this pronounced disturbance of the carbon cycle we studied a Late Barremian to Early Aptian neritic carbonate succession deposited on the northern Tethyan shelf (Swiss Alps). The sedimentological and stable carbon and oxygen isotope records of two sections located along a N–S transect from proximal to more distal shelf environments were investigated. The sediments correspond to outer-, mid-, and inner-ramp deposits of a homoclinal carbonate ramp. Vertical facies variations within the two studied sections feature three progradation phases of the platform. A highly resolved correlation of the shelf sediments with a pelagic succession from the Southern Alps (Northern Italy) is based on both δ13C stratigraphy and biostratigraphy, and indicates that the drowning of the Helvetic carbonate platform coincided with a pronounced calcification crisis of calcareous nannofossils. The biocalcification crisis started before but culminated during the Aptian methane event recorded in a negative carbon-isotope spike. We propose that increased carbon dioxide concentrations in oceans and atmosphere related to volcanic activity and to sudden methane release reduced the marine calcium carbonate oversaturation and the calcification potential of benthic and planktonic organisms. Carbonate-producing shallow water communities on platforms and ramps suffering from additional environmental stress such as extreme temperatures or high nutrient levels could not survive during times of rising sea level, and, as a consequence, carbonate platforms drowned.
Keywords: Carbonate platform; biocalci¢cation; Early Cretaceous; carbon dioxide; carbon isotopes; Mesozoic::Cretaceous::Lower::Aptian; Mesozoic::Cretaceous::Lower::Barremian; Мезозой::Меловая::Нижний::Барремский; Мезозой::Меловая::Нижний::Аптский